The Malay cultural landscape of Kutai Houses / Ahmad Zamil Zakaria, Nur Huzeima Mohd Hussain and Suriati Ahmad - Zakaria, Ahmad Zamil; Mohd Hussain, Nur Huzeima; Ahmad, Suriati (Universiti Teknologi MARA, Perak, 2021)
The 'Malays cosmology' focuses on principles of belief, the world of thought, and culture. Concerning the Malay landscape, this research is a continuation of previous findings. This study aims to obtain a list of landscape elements and their arrangements in the Kutai house (KH) style compound, located in the Perak Tengah District. On the other hand, the study was conducted to determine each landscape design elements' function, layout, and composition. It exposes the identity of the Malay landscape and indirectly enhances the community's self-esteem. It is possible to broaden the Malay Garden concept (MGC) identity and image. The finding showed a significant resultthat illustrated this concept is inconsistent as it has been subject to several interpretations and makes it challenging to explore scientifically